2014
DOI: 10.1088/2041-8205/788/1/l14
|View full text |Cite
|
Sign up to set email alerts
|

Sn 2008d: A Wolf-Rayet Explosion Through a Thick Wind

Abstract: Supernova (SN) 2008D/XRT 080109 is considered to be the only direct detection of a shock breakout from a regular SN to date. While a breakout interpretation was favored by several papers, inconsistencies remain between the observations and current SN shock breakout theory. Most notably, the duration of the luminous X-ray pulse is considerably longer than expected for a spherical breakout through the surface of a type Ibc SN progenitor, and the X-ray radiation features, mainly its flat spectrum and its luminosi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 27 publications
4
52
0
Order By: Relevance
“…It seems that the pre-explosion outbursts of CCSNe are common (e.g., Moriya et al 2014;Ofek et al 2014;Svirski & Nakar 2014;Tartaglia et al 2016;Yaron et al 2017), with about one in ten CCSNe suffering a pre-explosion outburst (e.g., Margutti et al 2017). The outburst might result from a single-star process, e.g., strong convection in the pre-collapsing core (Quataert & Shiode 2012;Shiode & Quataert 2014).…”
Section: Observational Consequencesmentioning
confidence: 99%
“…It seems that the pre-explosion outbursts of CCSNe are common (e.g., Moriya et al 2014;Ofek et al 2014;Svirski & Nakar 2014;Tartaglia et al 2016;Yaron et al 2017), with about one in ten CCSNe suffering a pre-explosion outburst (e.g., Margutti et al 2017). The outburst might result from a single-star process, e.g., strong convection in the pre-collapsing core (Quataert & Shiode 2012;Shiode & Quataert 2014).…”
Section: Observational Consequencesmentioning
confidence: 99%
“…A precursor to the SN explosion has been identified in the H-stripped type-Ibn SN 2006jc, which showed signs of interaction with a He-rich medium (e.g., Foley et al 2007;Pastorello et al 2007;Immler et al 2008). Evidence for significantly enhanced mass loss timed with the explosion has been found for the H-poor progenitors of both type-IIb SNe (GalYam et al 2014;Kamble et al 2015;Maeda et al 2015) and type-Ib SNe (Svirski & Nakar 2014), as well as for the H-and He-poor progenitors of type-Ic SNe associated with some nearby gamma-ray bursts (Margutti et al 2015;Nakar 2015). Along the same line, it is relevant to mention the possible detection of an outburst from the progenitor of the broad-line type-Ic SN PTF11qcj ∼2.5 years before stellar death (Corsi et al 2014), a possible precursor in the type-IIb SN 2012cs (Strotjohann et al 2015), and the recent detection of interaction of the H-poor superluminous SN iPTF13ehe with H-rich material at late times (Yan et al 2015), as well the evidence for significant temporal variability in the radio lightcurves of Ib/c SNe (Soderberg 2007;Wellons et al 2012), which suggests significant structure in their circumstellar media (CSM).…”
Section: Introductionmentioning
confidence: 99%
“…A CS may have formed before SB for SN 2008D/XRF 080109, assuming a progenitor with the parameters proposed in Reference [34]. This gives another important reason to search for SN 2008D-like events in the future.…”
Section: Discussionmentioning
confidence: 96%
“…We suggest here that the CS may have formed before SB for SN 2008D/XRF 080109. Svirski & Nakar [34] proposed that the progenitor was a Wolf-Rayet star surrounded with a moderately thick wind (r br 10 r * ). They suggested that the progenitor underwent enhanced mass-loss prior to the explosion, for 10 d, with mass-loss rate…”
Section: Sn 2008d / Xrf 080109mentioning
confidence: 99%